When Should There Be Vertical Choice in Health Insurance Markets? - Marone, Victoria R.; Sabety, Adrienne (American Economic Review, 2022)
We study the welfare effects of offering choice over coverage levels-"vertical choice"-in regulated health insurance markets. We emphasize that heterogeneity in efficient coverage level is not sufficient to motivate choice. When premiums cannot reflect individuals' costs, it may not be in consumers' best interest to select their efficient coverage level. We show that vertical choice is efficient only if consumers with higher willingness-to-pay have a higher efficient level of coverage. We investigate this condition empirically and find that as long as a minimum coverage level can be enforced, the welfare gains from vertical choice are either zero or economically small.